Global Environmental Governance Social-Ecological Perspectives - Bruckmeier, Karl.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book provides a critical review of global environmental governance as part of the broader process of sustainably transforming modern society. The author argues for substantial modifications, outlining potential improvements in knowledge bridging processes, integration and synthesis that offer valuable information for environmental policy and governance. These improvements, he argues, should be achieved through the use of theoretical and empirical knowledge gleaned from global scenario analysis and interdisciplinary environmental research, and with the aid of new practices for knowledge sharing, cooperation and collective learning. The analysis presented in the book is based on recent developments in social ecology and the author's interdisciplinary theory of society-nature interaction (Social-Ecological Transformation: Reconnecting Society and Nature, Palgrave Macmillan, 2016).
Chapter 1. Introduction -- Part I: The global environmental situation -- Chapter 2. Environmental change: Human modification of nature - social and environmental consequences -- Chapter 3. Social change: Social agency and human relations with nature in the industrial society -- Chapter 4. Policy change: Crisis of environmental policy and global governance -- Part II: Knowledge for renewing environmental governance -- Chapter 5. Environmental research and governance: Institutional problems of bridging knowledge divides and communicating science -- Chapter 6. Interdisciplinary knowledge integration for environmental governance: Epistemological questions -- Chapter 7. Social-ecological theory and global environmental governance -- Part III: Towards the future society: World ecology and changing societal relations with nature -- Chapter 8. Global environmental change and the transformation of the earth system -- Chapter 9. Beyond globalisation: Another transformation of the economic world system -- Chapter 10. Rethinking and renewing global environmental governance as part of social-ecological transformation.
Keywords: Environment; Physical geography; Environmental management; Human geography; Environmental policy; Environmental Sciences; Physical Geography; Environmental Management; Human Geography; Environmental Policy